Sex- and age-specific effects on the development of addiction and compulsive-like drinking in rats - Foo, Jerome Clifford; Skorodumov, Ivan; Spanagel, Rainer; Meinhardt, Marcus W. (Biology of sex differences, 2023)
Biological factors are known to influence disease trajectories and treatment effectiveness in alcohol addiction and preclinical and clinical evidence suggests that sex is an important factor influencing disease dynamics in alcohol dependence. Another critical factor is age at first intoxicating drink, which has been identified as a risk factor for later alcohol binging. Preclinical research allows prospective monitoring of rodents throughout the lifespan, providing very detailed information that cannot be acquired in humans. Lifetime monitoring in rodents can be conducted under highly controlled conditions, during which one can systematically introduce multiple biological and environmental factors that impact behaviors of interest.
Veröffentlicht: 07. Juli 2023
Gesehen am 17.08.2023